SİSTEMİK SKLEROZ VE PRİMER RAYNAUD SENDROMUNDA ANJİOTENSİN 1-7, ALAMANDİN, MRGD DÜZEYLERİ - DEMİRKOL, ALPER (Fırat Üniveristesi, 2023)
Bu çalışmanın amacı sistemik skleroz (SSk) ve primer Raynaud fenomeni (RF) hastalarında Raynaud Durum Skoru günlüğü (RDS) ile hastalık şiddetini ölçerek serum Anjiotensin 1-7, Alamandin ve MrgD düzeylerini sağlıklı kontrol grubu bireylerle karşılaştırıp SSk ve Primer RF'de bu moleküllerin klinik önemlerini belirlemektir. Çalışmaya ACR/EULAR 2013 sınıflama kriterlerine göre tanı almış 30 SSk tanılı hasta, İnternational Consensus kriterlerine göre tanı almış 30 primer Raynaud tanılı hasta ve 30 sağlıklı kontrol grubu alınarak karşılaştırılmıştır. Hastalık şiddetini ve aktivitesini değerlendirmek için hastalık aktivite skoru RDS hesaplandı. Serum Anjiotensin 1-7, Alamandin ve MrgD düzeyleri ELISA yöntemiyle ölçüldü. SSk, Primer RF tanılı hastalar ve kontrol grubunda serum Anjiotensin 1-7 düzeyleri arasında istatistiksel açıdan anlamlı farklılık saptanmamıştır (p=0.129). SSk, Primer RF ve sağlıklı kontrol grubundan elde edilen Alamandin düzeyleri istatistiksel farklılık göstermemektedir (p=0.075). Elde edilen serum MrgD düzeyleri SSk, Primer RF ve sağlıklı kontrol grupları arasında istatistiksel olarak farklılık göstermektedir (p=0.002). SSk MrgD düzeyi, RF ve sağlıklı kontrol grubu bireylerden farklılık göstermektedir (p=0.002). SSk'de RDS ortalama değeri Primer RF'den yüksek olarak saptanmıştır (p<0.001). RDS ile Anjiotensin 1-7, Alamandin, MrgD arasındaki ilişki incelendiğinde elde edilen veriler istatistiksel olarak anlamlı bulunmuştur. Bu nedenle vazokonstriktör etkili Anjiotensin 1-7, Alamandin ve MrgD düzeylerinin RF ve patogenezini açıklamaya yol gösterebilecek parametreler olabileceğini düşünmekteyiz. Ancak bu bulguları doğrulamak için katılımcı sayısının fazla olduğu, coğrafi olarak daha geniş bir alanda daha kapsamlı çalışmalar yapılması gereklidir. Anahtar Kelimeler: Sistemik Skleroz, Primer Raynaud, Anjiotensin 1-7, Alamandin, MrgD

The aim of this study was to measure the severity of the disease with Raynaud Condition Score diary (RCS) in Systemic Sclerosis (SSc) and Primary Raynaud patients, and to compare serum Angiotensin 1-7, Alamandin and MrgD levels with healthy control group individuals and to determine the clinical significance of these molecules in SSc and Primary RF. 30 patients with SSc diagnosed according to ACR/EULAR 2013 classification criteria, 30 patients with primary Raynaud's diagnosis diagnosed according to International Consensus criteria and 30 healthy control groups were included in the study. Disease activity score RCS was calculated to assess disease severity and activity. Serum Angiotensin 1-7, Alamandin and MrgD levels were measured by ELISA method. There was no statistically significant difference between serum Angiotensin 1-7 levels in patients with SSc, Primary RF and control group (p=0.129). Alamandin levels obtained from SSc, Primary RF and healthy control groups did not show statistical difference (p=0.075). The obtained serum MrgD levels differed statistically between SSc, Primary RF and healthy control groups (p=0.002). SSc MrgD level differs from RF (p=0.002) and SSc MrgD level differs from healthy control group individuals (p=0.002). It was determined that there was a statistical difference between the mean RCS values according to the diagnoses (p<0.001). RCS mean value in SSc differs significantly from Primary RF (p<0.001), RCS mean value in SSc differs significantly from healthy control group individuals, and Primary RF mean value differs significantly from healthy control group individuals (p<0.001). It was also found that there was no statistically significant difference between the levels of Angiotensin 1-7, Alamandin and MrgD when looked at by gender, regardless of disease or healthy control group. When the relationship between Raynaud Condition Score and Angiotensin 1-7, Alamandin, MrgD was examined, the data obtained were found to be statistically significant. Therefore, we think that the vasoconstrictor-acting Angiotensin 1-7, Alamandin and MrgD levels may be parameters that can guide the diagnosis of the disease and explain the pathogenesis. However, in order to confirm these findings, more comprehensive studies are required in a geographically wider area with a large number of participants. Keywords: Systemic Sclerosis, Primary Raynaud's, Angiotensin 1-7, Alamandin, MrgD
Angiotensin 1-7, alamandin, MRİ levels in systemic sclerosis and primary raynaud syndrome
Keywords: İç Hastalıkları